Contrasting hydrological response of coastal and desert biocrusts. Issue 2 (5th November 2012) - Kidron, Giora J.; Büdel, Burkhard
Abstract Biocrusts abound in southern Israel, covering the Hallamish dune field near Nizzana (NIZ) in the Negev (mean annual precipitation of 95 mm) and the coast of Nizzanim (NIM) near Ashdod (mean annual precipitation of 500 mm). While the hydrological response of the NIZ crust to natural rain events was thoroughly investigated, no data is available on the hydrological response of the NIM crust. Runoff was monitored in runoff plots during the years 2005–2008, and in addition, sprinkling experiments were carried out on NIM and NIZ crusts. For the evaluation of the possible factors that may control runoff initiation, fine content of the parent material, crust thickness, compressional strength, hydrophobicity, surface microrelief, organic matter, biomass (chlorophyll a and total carbohydrates) and the crust's species composition of NIM were studied and compared to that of NIZ. The data showed that in comparison to the NIZ crust that readily generated runoff, no runoff was produced by the NIM crust. This was so despite the fact that (1) Microculeus vaginatus predominated in both crusts, (2) the substantially higher rain intensities in NIM, (3) the greater thickness and higher chlorophyll content and (4) the lower microrelief at NIM in comparison to NIZ. The lack of runoff in NIM was explained by its low amounts of exopolysaccharides that did not suffice to affectively clog the surface and in turn to facilitate runoff initiation. The absence of runoff and its consequences on the NIM ecosystem are discussed. Copyright © 2012 John Wiley & Sons, Ltd.